A Review of Optimization Models and Techniques for Maintenance Decision Support Systems in Small and Medium Industries - Tahir, Zulkifli; M.A., Burhanuddin; Anton, S P; Haron, Habibollah (Electrical Engineering and Informatics Conference, 2008)
There are not many sufficient studies made on the application of artificial intelligence techniques to access troubleshooting activities as it always taken into consideration in a verbal sense and yet is not dealt with mathematically. The proposed study extended Choy, John, Thomas & Yan [1] models using either semi-parametric or non-parametric approaches of reliability analysis to examine the relationship between repair time and various risk factors of interest. Then the models will be embedded to neural networks to provide better estimation of repairing parameters. The proposed models can be used by maintenance managers as a benchmarking to develope quality service to enhance competitiveness among service providers in corrective maintenance field. Also the models can be deployed farther to develop a computerized decision support system